Analysis of the Implementation of Patient Guidance of Fall Risk at X Hospital - AT Titis Ayu Wulandari (Universitas Muhammadiyah Yogyakarta, 2017)
The objectives of this study are to find out the knowledge concerning the guidelines fall risk to the patients, to find out the ability of the nurses in the simulation of the guiding steps for the risk for falls, to find out the conformity of the review on the medical records of the patients, and to find out the obstacles in preventing risk for falls. It is a mix method study, which is a quantitative method with cross-sectional approach, and qualitative method with descriptive research design. The population of this study were 37 respondents for the quantitative research and 9 informants for the qualitative research. The results of the questionnaire indicate the presence of knowledge that most have fair criteria that is as much as 46%. The results of the medical record study show most of the full or compliant as much as 89.2%. While the structured interview showed different results. The conclusions of this study were that there was sufficient knowledge but lacked of discipline in completing the medical records, and there were still some obstacles in implementing the guidelines for risk for falls.